Stability analysis for mamdani-type integral fuzzy-based sliding mode control of systems under persistent disturbances - Prieto-Entenza, Pablo José; Aguilar, Luis T.; Cardenas-Maciel, Selene L.; López Rentería, Jorge Antonio; Cazarez-Castro, Nohe Ramon (My University, 2022)
Unmatched disturbances affect most of the mechanical systems, and finding conditions in the controllers for its attenuation still represent a challenge. We present sufficient conditions to guarantee asymptotic stability of single-input single-output systems driven by integral fuzzy-based sliding mode control. The stability analysis made in the Lyapunov framework gives the tuning conditions of the fuzzy system to preserve the robustness against bounded persistent, matched and unmatched disturbances. The theoretical results are numerically and experimentally validated in a one-link pendulum.
The IEEE Transactions on Fuzzy Systems
Keywords: Integral fuzzy based sliding mode control; Stabilyti analisis; Persistent disturbances; Campus Tijuana